ANALISIS KEKUATAN PEMBUKTIAN VISUM ET REPERTUM SEBAGAI BUKTI DALAM TINDAK PIDANA PEMERKOSAAN - Salafiyyah Diwayanti; Arsyad Aldyan (Sebelas Maret University, 2023)
This study aims to explain how the strenght of evidence (bewijskracht) for Visum et Repertum as evidence in the crime of rape in Decision Number 42/Pid.B/2021/PN.Kds. The research method used is a normative legal research method with a prescriptive nature of research and uses a case approach. This research shows that Visum et Repertum is important as evidence in the crime of rape because it plays a role in the process of proving a criminal case which can provide a clear picture of crime. Strenght of Evidence (bewijskracht) for Visum et Repertum in Decision Number 42/Pid.B/2021/PN.Kds is independent for the judge. The evidence presented in this case in the form of witness testimony, defendant’s statement, Visum et Repertum letter are related to one another. The strenght of the evidence is the same, no one exceeds the other. The strenght of the proof is free and not binding, depending on the judges’s assesment Keywords: Strenght of Evidence, Visum et Repertum